Revision of the bark louse genus Ceratostigma Li, 2002 (Psocodea: Psocidae: Psocinae) with description of a new species from China - Jie, Lulan; Liang, Feiyang; Liu, Xingyue (Zootaxa, 2022)
The bark louse genus Ceratostigma Li, 2002 is revised with description of Ceratostigma stagona sp. n., from Xizang Autonomous Region, China. A new combination of an Indonesian endemic species, C. lisae (Thornton, 1984) comb. n., is proposed, and thus Ceratostigma is newly recorded from Indonesia. A distribution map and a key to species of Ceratostigma are also provided.